Impact of EMU on Selected Non-European Union Countries - Desruelle, Dominique (Occasional Papers; Occasional Paper ;, 1999)
In the Summer of 1998, the Executive Board discussed a set of three papers prepared by the staff that focused on the likey impact of EMU on selected non-EU countries. In recognition of the contribution these papers could make to the literature and discussion of EMU, the Board requested that this collection of papers be published. This Occasional Paper presents the three papers in one volume Chapter 1 provides an analysis of the likely impact of EMU on three regions: Central and Eastern Europe, the Mediterranean Basin, and the African CFA zone. Chapter 2 focuses on the trade and financial effects of EMU on selected transition and Mediterranean countries. And Chapter 3 considers the possible implications of EMU for the Middle East and North Africa region.